PENGATURAN HUKUM TERHADAP TINDAK PIDANA PENYELUNDUPAN SATWA LANGKA BERDASARKAN HUKUM POSITIF DI INDONESIA - Ni Kadek Shintia Meiga Viani; Ida Bagus Gede Subawa (Jurnal Hukum Mahasiswa, 2023)
Indonesia is an archipelagic country which is famous for its diversity of endangered species protected by the government and is also a habitat for endemic animals which means that it has its own characteristics in each area and cannot be found in other areas. The legal arrangement for the crime of smuggling of endangered species based on positive law in Indonesia is the protection provided in legislation, which aims to prevent extinction and threats to the development of endangered species, their existence begins to be threatened as a result of conflict and poaching. This research is a normative research that examines laws and regulations in order to find out how the legal arrangements for the criminal act of smuggling endangered species are based on Indonesian positive law along with its legal sanctions. Based on the results of the research, criminal sanctions for the crime of smuggling endangered species based on positive law in Indonesia are contained in Article 40 paragraph (2) and paragraph (4) of the KSDA Law, in the form of imprisonment and fines, imprisonment and fines, plus the confiscation of all items obtained and all tools or objects used to commit criminal acts, with a statement that they are confiscated for the state.